ANALISIS PENERAPAN PROBLEM BASED LEARNING BERORIENTASI HOTS BERBANTUAN TEKNOLOGI DIGITAL DALAM PEMBELAJARAN BIOLOGI DI SMAN 17 MEDAN - Gresia Sinaga; Louisa Assian Sinaga; Maria Shintauli Panggabean; Marbun, Yolanda; Widya Arwita; Rizal Mukra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of Problem Based Learning (PBL) oriented toward Higher Order Thinking Skills (HOTS) supported by digital technology in biology learning at SMAN 17 Medan. This research used a qualitative descriptive approach with a structured interview technique involving a biology teacher as the main informant. Data were collected through interviews focusing on the implementation of PBL, the use of digital technology, the application of HOTS-based learning, and the integration of Technological Pedagogical Content Knowledge (TPACK) in classroom activities. The results showed that the implementation of PBL began with presenting contextual problems related to students’ daily lives, followed by group discussions, information exploration, and presentation of solutions. The use of digital technology such as Google Classroom, PowerPoint, learning videos, and internet-based resources supported the learning process and helped students understand abstract biological concepts more effectively. The integration of HOTS was reflected in analytical questions, case-based assignments, and collaborative discussions that encouraged critical thinking and problem-solving skills. Furthermore, the integration of TPACK was evident from the teacher’s ability to combine content mastery, appropriate pedagogical strategies, and digital technology use. However, several challenges were found, including limited instructional time, inadequate technological facilities, and differences in students’ digital literacy skills.